Development Of The Maorif System During The Era Of The Shaybanids - Abdug'afforova, Mohinur (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
This article scientifically analyzes the formation of the education and enlightenment system in Movarounnahr  during the Shaybanid dynasty, the role of madrasahs in social life, and their contribution to the development of science. The study, using historical sources and modern scientific literature, highlights the specific aspects of the education system during the Shaybanid era, the activities of educational institutions, and issues of state patronage.